Ethnobotanical survey of medicinal plants from Ilam District, East Nepal - Bhattarai, Krishna Ram; Khadka, Madan Kumar (Our Nature, 2017)
An ethnobotanical survey was carried out on the utilization of medicinal plants by Brahman and Chhetri of Nayabazar VDC of Ilam District, East Nepal by interviewing traditional herbalists and various elderly men and women in April and May 2014. All together 102 plant species were recorded for their uses to cure at least 56 human ailments. These species, belonging to 64 families, are listed in alphabetical order, each with local name, parts used, methods of preparation and dose, route of administration, and local status of the plant. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.